[OP.LB03.07] EFFECTS OF LERCANIDIPINE/ENALAPRIL COMPARED WITH AMLODIPINE/ENALAPRIL AND HYDROCHLOROTHIAZIDE/ENALAPRIL ON TARGET ORGAN DAMAGE AND SYMPATHETIC ACTIVITY IN HYPERTENSION. (September 2016) - Tsioufis, C.; Kasiakogias, A.; Dimitriadis, K.; Kalos, T.; Liatakis, I.; Konstantinidis, D.; Andrikou, E.; Nikolopoulou, L.; Vlachos, E.; Kyriazopoulos, K.; Tousoulis, D.
Abstract : Objective: The aim of the study is to compare in essential hypertensives the effects of lercanidipine/enalapril versus amlodipine/enalapril and enalapril/hydrochlorothiazide on various target organ damage end-points as well as on sympathetic nervous system activation during a follow-up period of 3 months. Design and method: We studied 56 untreated patients with essential hypertension stage II [age: 56 ± 10 years, 30 males, office blood pressure (BP): 148/92 ± 14/11 mmHg] who were randomized to lercanidipine 10 mg/enalapril 20 mg (once daily) or amlodipine 5 mg/enalapril 20 mg (once daily) or enalapril 20 mg/hydrochlorothiazide 12.5 mg (once daily) with a ratio 1:1:1. At baseline and 3 months follow-up arterial stiffness was evaluated on the basis of carotid to femoral pulse wave velocity (PWV) while sympathetic drive was assessed by muscle sympathetic nerve activity (MSNA) estimations. Moreover, albumin to creatinine ratio (ACR) and renal resistive index (RRI) were assessed. Results: Patients on lercanidipine/enalapril (n = 19), amlodipine/enalapril (n = 18) and enalapril/hydrochlorothiazide ivabradine (n = 19) did not differ regarding baseline BP, creatinine, glucose and lipid profile (p = NS for all). There were also no significant differences in the reduction of office as well as ambulatory BP between groups (p = NS). In all treatment groups RRI and PWV levels were favorably reduced (p < 0.001 for all). However, hypertensive patients in the lercanidipine/enalapril group were characterized by a reduction in ACR from 60.4 ± 65.5 to 29.9 ± 27.1 mg/g (p < 0.05), whereas ACR was not altered in all other treatment groups. In the lercanidipine/enalapril group, MSNA was decreased from 71.5 ± 7.4 bursts per 100 heart beats to 65 ± 8.2 bursts per 100 heart beats (p < 0.001) at 3 months and in the amlodipine/enalapril group from 66.7 ± 7.3 bursts per 100 heart beats to 65.5 ± 7.4 bursts per 100 heart beats (p < 0.05). No significant changes in MSNA was observed in the enalapril/hydrochlorothiazide group (p = NS). Conclusions: In hypertensive patients lercanidipine/enalapril therapy reduces ACR in contrast to amlodipine/enalapril and enalapril/hydrochlorothiazide which exert no beneficial effect. Moreover, there is a greater decrease of MSNA by lercanidipine/enalapril compared to amlodipine/enalapril, while enalapril/hydrochlorothiazide does not alter sympathetic drive.